Developing a conceptual framework for digital economy competencies among managerial-level employees in Malaysia’s manufacturing sector - Morshidi, Zainal Abiddin; Hussin, Norhayati; Ahmad, Masitah; Osman, Suhaila; Tokiran, Nurul Syfa’; Mohd Zazmi, Muhammad Zaffri (International Journal of Accounting, Finance and Business, 2026)
In Malaysia, the manufacturing sector, a key pillar of economic growth, faces significant challenges in digital transformation due to gaps in managerial-level digital competencies. Despite various government-led initiatives aimed at upskilling and reskilling, empirical evidence indicates that a substantial proportion of managers remain underprepared for the demands of the digital economy. This study develops a conceptual framework for digital economy competency at the managerial level within the Malaysian manufacturing sector, grounded in the Resource-Based View (RBV) and Dynamic Capability Theory. This study employed a quantitative cross-sectional survey design, and data were collected from 385 respondents using a structured questionnaire distributed to managerial employees in manufacturing firms in Sarawak, particularly those involved in digital technology adoption across subsectors such as electronics, food manufacturing, chemicals, wood-based production, and renewable energy. A simple random sampling technique was used to ensure equal selection probability and minimise bias. The findings revealed four core competency domains, which are communication, digital literacy, digital governance, and digital infrastructure, that collectively underpin managerial readiness for digital transformation. Notably, the proposed framework not only offers theoretical insights by positioning digital competency as a strategic organizational capability but also enhances practical applicability through the identification of measurable indicators for each domain. By bridging global best practices with the contextual realities of Malaysia’s manufacturing sector, this study contributes to the literature on digital competency development and provides a practical diagnostic tool for organizations and policymakers. This framework serves as a foundation for future empirical validation and supports workforce transformation in alignment with Industry 4.0 and Industry 5.0 agendas.